Peer effects in the decision to apply for a professional excellence award - Samuel G. Berlinski; Alejandra Ramos (Inter-American Development Bank (IDB), 2020)
We study the role social interactions at the workplace play in the decision to apply for a professional recognition program. In Chile, teachers can apply to a pedagogical excellence award. Successful applicants receive a wage increase and are publicly recognized. We exploit the quasi-random variation in the allocation of awards generated by a sharp assignment rule. We document that the success of an applicant increases her school colleagues' application rate to the program by almost 75 percent. The impact is higher for colleagues with closer interaction with a successful applicant. We speculate on social learning as a driver of this result.
Keywords: J33; J58; M52; 330; Merit award; Public recognition; Peer effects; Social learning